Who Cares What She Thinks, What Does He Say? Links between Masculinity, In-Group Bonding and Gender Harassment. - Hunt, Christopher; Gonsalkorale, Karen (Sex Roles, 2014)
Previous research has linked threats to masculinity and gender harassment, the most pervasive form of sexual harassment. Using a computer harassment paradigm, an ingroup bonding explanation of this link was directly examined. The study was conducted with heterosexual male undergraduate students from an inner city Australian university. Participants received a threat to masculinity before being exposed to an ostensible gender ingroup member whose reaction to sexist jokes was manipulated. Data from 74 participants revealed that men high on conformity to masculine norms altered their behavior to correspond with feedback from the gender ingroup member after a masculinity threat, whereas men low on conformity to masculine norms rejected gender ingroup feedback after a masculinity threat. A variable examining reported liking of the gender ingroup member produced a similar pattern, while no changes were observed in reported liking of a gender outgroup member These results suggest that the perceived response of other members of the gender ingroup, but not members of the gender outgroup, influence men's proclivity to enact gender harassing behaviors.